Satisfaction received towards agricultural information from television programs among farmers - Ramli, Nor Sabila; Hassan, Md. Salleh; Abu Samah, Bahaman; Shahkat Ali, Muhamad Sham; Sabagpour, Zoheir (Science Publications, 2013)
Television is one of the top mass media to broadcast the information. It is heartening to know that mass media is playing its role in developing and strengthening the agriculture sector in Malaysia. Results from many international studies found that farmer received a high level of satisfaction from agriculture programs aired on television. However, can the similar results found among farmers in Malaysia? Therefore, this study intends to discover the Malaysian farmers satisfaction towards agricultural information aired on television. This is a quantitative study. The data collection was conducted through survey method and the respondents selected were from the states of western Malaysia Kedah and Selangor. Interestingly, both states; Kedah and Selangor recorded a similar level of satisfaction towards agriculture programs. Further analyses run have concluded that farmers in both states have a higher level of satisfaction towards information related to crops/livestock/farming and good agriculture practices. The findings of the study can be good sources and references for the agriculture programs producers to measure on the level of satisfaction of the agriculture programs aired by television among the farmers. Moreover, the findings demonstrated can help our agricultural programs producer to improve their contents in order to fulfill needs of their audience.